Mandibular Reconstruction With Fibula Flap and Dental Implants Through Virtual Surgical Planning and Three Different Techniques: Double-Barrel Flap, Implant Dynamic Navigation and CAD/CAM Mesh With Iliac Crest Graft - Antúnez-Conde, Raúl; Salmerón, José Ignacio; Díez-Montiel, Alberto; Agea, Marc; Gascón, Dafne; Sada, Ángela; Navarro Cuéllar, Ignacio; Tousidonis, Manuel; Ochandiano, Santiago; Arenas, Gema; Navarro Cuéllar, Carlos (Frontiers in Oncology, 2021)
Introduction Vertical discrepancy between the fibula flap and the native mandible results in difficult prosthetic rehabilitation. The aim of this study was to evaluate the outcomes of 3D reconstruction of the mandible in oncologic patients using three different techniques through virtual surgical planning (VSP), cutting guides, customized titanium mesh and plates with CAD/CAM technology, STL models and intraoperative dynamic navigation for implant placement. Material and methods Material and Methods Three different techniques for mandibular reconstruction and implant rehabilitation were performed in 14 oncologic patients. Five patients (36%) underwent VSP, cutting guides, STL models and a customized double-barrel titanium plate with a double-barrel flap and immediate implants. In six patients (43%), VSP, STL models and a custom-made titanium mesh (CAD/CAM) for 3D reconstruction with iliac crest graft over a fibula flap with deferred dental implants were performed. Three patients (21%) underwent VSP with cutting guides and customized titanium plates for mandibular reconstruction and implant rehabilitation using intraoperative dynamic navigation was accomplished. Vertical bone reconstruction, peri-implant bone resorption, implant success rate, effects of radiotherapy in vertical reconstruction, bone resorption and implant failure, mastication, aesthetic result and dysphagia were evaluated. Results Significant differences in bone growth between the double-barrel technique and iliac crest graft with titanium mesh technique were found (p<0.002). Regarding bone resorption, there were no significant differences between the techniques (p=0.11). 60 implants were placed with an osseointegration rate of 91.49%. Five implants were lost during the osseointegration period (8%). Peri-implant bone resorption was measured with a mean of 1.27 mm. There was no significant difference between the vertical gain technique used and implant survival (p>0.385). Implant survival rates were higher in non-irradiated patients (p<0.017). All patients were rehabilitated with a fixed implant-supported prosthesis reporting a regular diet (80%), normal swallowing (85.7%) and excellent aesthetic results. Conclusions Multi-stage implementation of VSP, STL models and cutting guides, CAD/CAM technology, customized plates and in-house dynamic implant navigation for mandibular defects increases bone-to-bone contact, resolves vertical discrepancy and improves operative efficiency with reduced complication rates and minimal bone resorption. It provides accurate reconstruction that optimizes implant placement, thereby improving facial symmetry, aesthetics and function.